Pengaruh Fasilitas Kerja Terhadap Kinerja Pegawai pada Kantor LPP RRI Ambon - Jessy Juniu Hahury (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
This study aims to find out how the influence of work facilities on employee performance at LPP RRI Ambon. The facilities in the entire workspace at the LPP RRI Ambon office in the HR section are 8 facilities needed and 6 facilities are in good condition and 2 are in bad condition. In general, there are 17 units of facilities needed and 10 facilities in good condition and 7 facilities in bad condition. Partial regression coefficient t test was conducted to determine the effect of each independent variable. To find out whether the null hypothesis is rejected and the alternative hypothesis is accepted or vice versa is tested by comparing the tsig value <α = 0.05, the independent variable has a significant effect on the dependent variable. Vice versa if tsig > α = 0.05 then the independent variable has no significant effect on the dependent variable. In the Finance section there are 18 units of facilities needed with 10 units of facilities in good condition and 8 in bad condition. Program Planning and Evaluation Section (Programming) where there are 23 units of facilities needed with 15 units of facilities in good condition and 8 units in bad condition. News review and communication (news) where there are 14 required facility units with 12 facility units in good condition and 2 in bad condition. Studio and New Media Engineering with 15 units of facilities needed and 13 units of facilities in good condition and 2 units of facilities in bad condition. Broadcasting and Public Service Infrastructure Engineering with 63 units of facilities needed with 52 units of facilities in good condition and 11 units of facilities in bad condition. From the explanation above, it can be concluded that work facilities are very important for the continuity of employee performance at LPP RRI Ambon.